Socialization of The Emotional Effect of Freedom Technique on The Anxiety of Pre-Percutaneous Coronary Intervention Patients in The Hospital Grandmed Lubuk Pakam - Syara, Arfah May (JURNAL PENGMAS KESTRA (JPK), 2023)
Coronary heart disease (CHD) is a health disorder in the cardiovascular system where cases have a mortality rate of 6.7 million cases in 2018. CHD is a dangerous disease in the Southeast Asian region, including Indonesia. The prevalence of CHD in North Sumatra is 0.5%. Percutaneous Coronary Intervention (PCI) action is a technique to open blood vessels and return blood through the coronary arteries. In carrying out proper PCI operations, interventions are needed that can reduce the anxiety of pre-PCI patients, namely The Emotional Freedom Technique (EFT). Service activities are carried out through outreach activities through several methods of lectures, discussions, and questions and answers. The number of participants in this PkM activity was 15 nursing staff at the Lubuk Pakam Grandmed Hospital. The sample was determined using a random sampling technique, where the sample of male nursing staff was 4 people and 11 female nursing staff. The activity begins with giving a pre-test and ends with a post-test. The results of the dedication show that the level of anxiety can be reduced by administering Emotional Freedom Technique (EFT) therapy. The percent increase in knowledge of the largest and smallest PkM participants is 25% and 15%. The average value of increasing the knowledge of PkM participants after being given socialization was 20%. This socialization activity has succeeded in providing benefits for PkM participants in increasing PkM participants' knowledge about the effect of EFT.